Marketing information and knowledge in boutique hotels: A qualitative study - Bunchua E. (2017)
The popularity of boutique hotels brings more intense competition to the hospitality industry in Chiang Mai, Thailand. The entrepreneurial hotel owners, who are mostly architects, introduced the unique designs, personalized accommodation and service facilities to differentiate themselves from conventional hotels, resorts and guesthouses. However, these entrepreneurs often lack a background of business and marketing, so they need to augment their marketing strategy in order to survive in an over-supply market. The success depends on the recognition of marketing information and transformation such information into marketing knowledge, which combines to the management experience. This study aims to investigate the current use of marketing information system (MkIS) in boutique hotels, and to identify the body of marketing knowledge which derives from the combination of personal experience and the available information. Most MkIS applications are designed to fit the requirements of large enterprises, while this study reflects the customization of marketing information and knowledge management system in the context of small boutique hotels in order to attract and retain their customers. © Common Ground, Ek Bunchua, Nopasit Chakpitak, All Rights Reserved.